Pre-clinical studies of Siddha formulations advocated for anaemia: A systematic review and meta-analysis - Arumugam Rajendra Kumar, Gayathri Gunalan, Khaja Hussain Hina Firdouse, Arivazhagan Archana (Journal of Applied Pharmaceutical Science, 2023)
Anaemia is a global burden that affects millions of people’s health and quality of life. It is one of the most severe and important nutritional deficiencies prevailing in the world. Siddha, a known system of Indian Medicine owns numerous medicinal preparations for the treatment of anaemia with literature evidences in many classical texts. To date, many clinical and pre-clinical trials have been carried out in Siddha formulations which were indicated for anaemia. This manuscript deals with the systematic review and meta-analysis of pre-clinical studies of various Siddha formulations used for the treatment of anaemia. The aim of the study was to compile and summarize the findings of all relevant pre-clinical studies of Siddha formulations used for treating anaemia. Data of pre-clinical trials of various haematinic Siddha formulations were retrieved from electronic databases like PubMed, Cochrane, Science Direct, Medline, Scopus, and Google scholar. Preferred reporting items for systematic review and meta-analysis guidelines were adopted for systematic review and RevMan 5.2 software was used for the meta-analysis. Systematic review demonstrated the difference in haemoglobin (Hb), red blood corpuscles (RBC) count and heavy metals levels in these Siddha herbal and herbo-mineral/herbo-metallic formulations. Meta-analysis has revealed significant increase in Hb and also in total RBC count after treatment with these Siddha Haematinics. The meta-analysis of toxicity studies also reveals that no toxic effects were observed up to the level of therapeutic dose. The outcome of this systematic review and meta-analysis demonstrated that great number of Siddha formulations has been available since ages for the treatment of anaemia and the same has been proved by various evidence based safety and efficacy studies. However, a well-designed randomized clinical trials of these Siddha interventions are need of the hour for the recognition of this traditional system of medicine in the treatment of anaemia globally.
Keywords: Anaemia, Siddha medicine, Veluppu noi, Pandu, pre-clinical studies, haematinics, RBC